Developing prospective teachers' science-task knowledge and practice through lesson study - Yuswa Istikomayanti; Zuni Mitasari; Anis Samrotul Lathifah; M. Mashuri; Pratika Desy (University of Muhammadiyah Malang, 2024)
Science learned requires constructivist experiences so that students could learnt to discover and conclude. However, today's learned challenges were increasing along with the diversity of students and interests. The aimed of this researched was to increase the knowledge and practiced of prospective science teachers in didactic practiced through lesson studied activities. Didactic knowledge and practiced includes aspects of knowledge in preparing student assignments and analyzing student learned difficulties. Apart from that, updating student competency achievements as a curriculum requirement was also a challenged for prospective teachers. This researched was a qualitative studied that conducted researched on the lesson studied group of prospective teachers consisting of two groups totaling eleven prospective teachers. Data collection was carried out through direct group observation, semi-structured interviews, and participant observation. The results of the implementation of the lesson studied project revealed the stages of science learned through the preparation of various learned ideas, the preparation of structured learned paths by thinking about the future, thinking about the process of student collaboration and the learned process. Constructed science concepts to determine objective learned outcomes. The results of this researched revealed how teams of prospective teachers collaborate in lesson studied learned and did things that built and support the team in achieving common goals.